INTEGRASI ETNOPEDAGOGI: TRANSFORMASI KEARIFAN LOKAL PERTANIAN DESA POJOK KABUPATEN KARANGANYAR SEBAGAI SUMBER BELAJAR KONTEKSTUAL - Sabrina Kartika Putri; Dwi Anggraeni Siwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the process of ethnopedagogy integration through the transformation of local agricultural wisdom in Pojok Village as a learning resource for Natural and Social Sciences (IPAS) for fourth graders, as well as teacher strategies in overcoming obstacles to its implementation at Pojok 01 Public Elementary School. This study used a qualitative method with a case study design, with subjects consisting of fourth-grade teachers and fourth-grade students. Data collection techniques included participatory observation, in-depth interviews, and documentation. Interactive data analysis was used as an analytical technique. The results showed that the curriculum transformation was carried out by synchronizing local agrarian wisdom, which was originally oral, into formal project-based teaching modules. Field learning applied the philosophical principle of "melakoni" (acting), with activities consisting of 30% theory and 70% hands-on practice. The constraint of limited school space was successfully overcome through an adaptive strategy of shifting planting media to polybags. Meanwhile, limited facilities were addressed through independent student participation by bringing tools from home, and time constraints were overcome by completing individual observation journals outside of school hours. This adaptive strategy proved not only to overcome technical obstacles but also effective in fostering students' independent character, sense of responsibility, and consistency in self-esteem.